Synthesis, Optimization, and Kinetic Studies of Sulfonated Palm Biomass Magnetic Biochar Catalyst for Biodiesel Production Using Used Cooking Oil - Mohiddin, Mohd Nurfirdaus Bin (Curtin University, 2023)
Magnetic biochar catalyst (MBC) utilization in biodiesel production can enhance the catalyst separation process and reusability. As MBC utilization is still on the laboratory scale and studies on the utilization of MBC are still limited, many aspects are still unknown. This research addressed the abovementioned research gaps. MBC was synthesized and characterized from oil palm biomass. The optimum MBC synthesis parameters were acquired. Optimized biodiesel production parameters using the synthesized MBC, the biodiesel characteristics, and the reaction kinetics were studied.